Turning the solubility and lubricity of ionic liquids by absorbing CO2. (May 2018) - Wu, Jian; Mu, Liwen; Zhu, Jiahua; Chen, Yifeng; Yin, Xiang; Feng, Xin; Lu, Xiaohua; Larsson, Roland; Shi, Yijun
Abstract: Ionic liquids (ILs) attract high interest as lubricants or lubricant additives due to their special physicochemical characteristics. CO2 is a widely distributed gas. In many situations, its influence on lubricants cannot be avoided. In this work, three ILs are synthesized from choline and amino acids of glycine, l -proline and lysine, respectively. The influence of CO2 absorption on their solubility and lubricity is investigated. In general, it is interesting to find that the solubility is decreased and their lubricity is obviously improved after absorbing CO2, which is strongly related to their functional group (amino group) interactions with CO2 . The formation of carbamate groups greatly increases the viscosity resulting in less solid contacts, and strengthens the interfacial adhesion between ILs and solids. Graphical abstract: Highlights: The influence of CO2 absorption on ionic liquid based lubricants was studied. The solubility of lubricants was decreased and the lubricity was greatly improved after absorbing CO2 . The formation of carbamate groups increases the viscosity resulting in less solid contacts. The interfacial adhesion between ILs and solids is strengthened by carbamate groups.